Perlindungan Konsumen atas Metode Penawaran Negative Option di Indonesia - Elizabeth Anastasia; Dwi Sekar Ningrum; William Marthianus; Willis Patrick Onggo (JURNAL MERCATORIA, 2019)
Negative Option Method is a bidding method that requires confirmation from consumers in accepting or rejecting an offer. If the customer doesn’t provide confirmation, the business actor assumes that the consumer agrees and will be charged a fee for the offer given. The Negative Option method originating from the United States has actually developed in Indonesia, especially in the provision of telecommunications services. It is not uncommon for Telecommunications Service Providers in Indonesia to offer a particular feature that requires confirmation of rejection or cancellation from consumers via message, such as "unreg". If the consumer does not provide confirmation, the business actor will unilaterally assume that the Customer has accepted the offer, thus often resulting in the consumer experiencing financial losses due to the imposition of costs for goods and / or services without the consent of the consumer. This encourages the author to conduct legal research on consumer legal protection of the Negative Option bidding method using the normative juridical method. This legal research concludes that the Negative Option bidding method is contrary to the Minister of Communications Regulation Article 2 paragraph (3) and Article 4 paragraph (1) letter a which specifies that each Telecommunications Service Provider must obtain written and/or message approval from the Customer to activate a paid feature. If the Telecommunications Service Provider has not received approval from the Customer, then the paid feature must be stopped.